What Helps, What Hinders? Undergraduate Nursing Students' Perceptions of Clinical Placements Based on a Thematic Synthesis of Literature - Robyn Cant PhD, MHlthSc; Colleen Ryan RN, BHlthSc, GCertCE, MHPE; Lynda Hughes RN BN, GDOrthNurs, GDCCNurs, MN, MEd, PhD; Elise Luders RN, RM, MMid, GCHPE, GDCCU; Simon Cooper RN, BA (Hons) (SAGE Publishing, 2021)
Introduction Clinical placements are a mandatory component of nursing students' education internationally. Despite clinical education being a key to nursing students' achievement of nursing competencies, few studies have reviewed students' narratives to describe their experiences of learning during clinical placement. Such studies may be important in offering a deeper insight into clinical learning experiences than quantitative surveys. Methods A s ystematic thematic synthesis of qualitative studies between 2010 and June 2020 was conducted. English language studies that offered a thematic analysis of undergraduate nursing students' experiences of learning during placement were sought. A search was made of five databases PubMed, Ovid Medline, CinahlPlus, SCOPUS, and Google Scholar. The study was guided by the ENTREQ statement for enhancing transparency in reporting the synthesis of qualitative research. Results Twenty-seven qualitative studies were included in the review. A thematic synthesis showed over 100 themes and subthemes across the studies. A cluster analysis revealed positive elements and others that were seen in the studies as a barrier (hindrance) to clinical learning. Positive elements included supportive instructors, close supervision, and belonging (in the team). Unsupportive instructors, a lack of supervision and not being included were seen as a hindrance. Three key overarching themes that could describe a successful placement were revealed as "Preparation," "Welcomed and wanted" and "Supervision experiences". A conceptual model of clinical placement elements conducive to nursing students' learning was developed to enhance understanding of the complexities associated with supervision. The findings and model are presented and discussed. Conclusion The conceptual model presents positive elements that influence students' clinical placement experiences of learning. This model may provide a framework to guide professional development programs and strategies to support students and supervisors alike, an important step forward in moving beyond the current clinical placement rhetoric.